Journal Club: Comparison of symptomatic and asymptomatic persons with Alzheimer disease neuropathology - Brosch, Jared R. (Lippincott Williams & Wilkins, 2014)
Advances in neuroimaging, biomarkers, and clinical data have led to the hypothesis that the pathologic process of Alzheimer dementia begins decades prior to functional decline and diagnosis.(1–3) High-profile clinical trial results have shown that biomarker changes can be made via pharmacologic intervention; however, the timing of this intervention has likely been too late to impact the cascade of neurodegenerative changes.(4,5) In “Comparison of symptomatic and asymptomatic persons with Alzheimer disease neuropathology” by Monsell et al.,(6) neuropathologic and clinical data were used to determine the risk of developing clinically significant cognitive impairment. This work represents a significant contribution because it examines a large cohort of autopsy data, which includes patients with Alzheimer dementia neuropathology who were clinically normal or diagnosed with mild cognitive impairment and Alzheimer-type dementia. The authors report a 3-fold increase in the risk of cognitive symptoms in association with quantifiable increases in neurofibrillary tangle pathology. Additionally, several other factors including APOE gene status, history of depression, and age impacted the clinical presentation. The ultimate goal of this investigation and similar studies is to facilitate the early and accurate identification of those at risk of developing Alzheimer dementia, such that potentially disease-modifying therapies may be considered.